A paráfrase no vestibular: uma prática de (re)formulação do dizer - Santos, Hélder Sousa (2010)
Under the theoretical perspective of the Linguistics of Enunciation, the subjectivity involved in the practice of paraphrase in vestibular was studied. Theorists such as Authier-Revuz (2004), Benveniste (1988, 1989), Flores (1999, 2005), Fuchs (1982, 1985, 1994), Milner (1987, 2006) Saussure (2006), Tfouni (2008), among others, founded the research. Specifically, eight texts produced by students were analyzed. Students were supposed to paraphrase enunciations of the so called motivating text (MT) that compounded the writing test of vestibular. It should be pointed out that, in order to produce these paraphrases, students should obey the rules previously given by the examiners. "Obey" is written in quotation marks because our analysis shows that there are effects of meanings which, certainly, reveal the production of other meanings that comes from the students attempt to produce the same meaning present in the motivating text. These other meanings produce a tension between the meanings accepted by correctors, in their reading of the MT, and those that are expunged, not accepted. In this tension, the subjectivity that involved the practice of paraphrase becomes visible, making it relevant to consider the paraphrase as a fact of enunciation, related to the semantics of speech, rather than to the formal approach vestibular attributes to it. Through our theoretical assumptions, we dealt with the idea that the paraphrase is nurtured by an imaginary investment of objectivity, maintained by vestibular procedures of evaluation. To what concerns this investment, the research was not worried, in any time, to justify the paraphrasing gestures of students according to the judgment of the two correctors of vestibular. By examining carefully the way these correctors evaluated the paraphrases written by students (italics, comments on each one), the analysis compared what one corrector considered as a paraphrase of enunciations of the MT of the writing test of vestibular to the posture of the other corrector who did not consider it as a correct paraphrase. Divergences were realized in the evaluation of the two correctors. However, they are not enough to say that they are the result of different ideas of each corrector on the concept of paraphrase. These divergences are actually the expression of different readings of students paraphrases each corrector had. In other words, they are related to the meanings each corrector recognized as being part or not of the MT of the writing test of vestibular. Thus, being the text, in an enunciation perspective, an incomplete object, which allows to represent mobile meanings, we consider that the paraphrase and, as a consequence, its recognition (or not) is, in our work, understood as something open, once it is subordinate to judgments of a subjective order of correctors who have, for example, different histories of reading. This is to say that there are issues of subjectivity present in the acts of recognition (or not) of paraphrase in the writing test of vestibular. Moreover, our study examines the possible relationship between gestures of paraphrase and traces of authorship, as a work (interpretation) of the scriptor on the MT and the enunciation position that builds and is built in the construction of the MT through reading.